2013
DOI: 10.1002/poc.3246
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structure, experimental and theoretical1H and13C NMR chemical shift assignment of cyclic and acyclic α,β-unsaturated esters

Abstract: The experimental 1H and 13C NMR spectra of 13 phenyl cinnamates and four 4‐methylcoumarins were investigated and their chemical shifts assigned on the basis of the two‐dimensional spectra. For the unsubstituted cinnamic acid phenyl ester, optimized molecular structures were calculated at a B3LYP/6‐311++G(d,p) level of theory. 1H and 13C NMR chemical shifts were also calculated with the GIAO method at the B3LYP/6‐311 + G(2d,p) level of theory. The comparison between experimental and calculated NMR chemical shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In a previous work, phenyl esters of cinnamic acid showed that the Z conformation was 4.91 kcal mol À1 more stable than its E counterpart. [10] The E p curve around torsion C angle shows only one minimum at 08 as the E conformer forces both aromatic rings to get close to each other (repulsive effect). The E p difference between the two conformers, i.e.…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…In a previous work, phenyl esters of cinnamic acid showed that the Z conformation was 4.91 kcal mol À1 more stable than its E counterpart. [10] The E p curve around torsion C angle shows only one minimum at 08 as the E conformer forces both aromatic rings to get close to each other (repulsive effect). The E p difference between the two conformers, i.e.…”
Section: Theoretical Calculationsmentioning
confidence: 99%